A needs assessment study of what health care consumers seek from social media and social networking. Issue 4 (2nd October 2018) - Cangelosi, Joe; Kim, David; Ranelli, Ed; Griffin, Ken
Abstract: Given that prevention is crucial to long healthy life and restraining escalating health care costs, this study examines social media and networking (SM&N) needs among health consumers regarding preventive health. Results showed the most important SM&N needs included: education about health issues, connecting to a support group, knowing the implications of health condition, opportunities and understanding of preventive health care, and tracking physical activity. Among demographic groups women, younger aged groups, and African Americans considered SM&N needs to be more important. Homemakers indicated greatest need for information about health issues and facilitating interaction with others. Full-time employees placed greater importance on managing their own health.